Area of 16S ribonucleic acid at or near the interface between 30S and 50S ribosomes of Escherichia coli. - Santer, M (1977)
To determine the region of 16S ribonucleic acid (RNA) at the interface between 30 and 50S ribosomes of Escherichia coli, 30 and 70S ribosomes were treated with T1 ribonuclease (RNase). The accessibility of 16S RNA in the 5' half of the molecule is the same in 30 and 70S ribosomes. The interaction with 50S ribosomes decreases the sensitivity to T1 RNase of an area in the middle of 16S RNA. A large area near the 3' end of 16S RNA is completely protected in 70S ribosomes. The RNA near the 3' end of the molecule and an area of RNA in the middle of the molecule appear to be at the interface between 30 and 50S ribosomes. One site in 16S RNA, 13 to 15 nucleotides from the 3' end, normally inaccessible to T1 RNase in 30S ribosomes, becomes accessible to T1 RNase in 70S ribosomes. This indicates a conformational change at the 3' end of 16S RNA when 30S ribosomes are associated with 50S ribosomes.